(untitled) (Patan Pragya, 2025)
Corporate social responsibility plays a very important role in the banking sector and it is the most valuable asset of any. The funds collected from the account holders are used for organization. When profitable banks perform the long last, they perform the task better. Because now a days dynamic business environment, where banks are presented with challenges regarding profit in the banking sectors. This paper analyze the effects of CSR on the financial performance of commercial banks in Nepal. The target population of the study has been 20 commercial banks out of only 10 banks are sample using the judgmental sampling technique. All secondary data collected from sample banks through annual reports between 2015 and 2023. Causal comparative research design are applied to analyze. Analyze is carried out by SPSS 26 version. Dependent variables return on assets, return on equity. Whereas the independent variables are cultural heritage, education, health, financial literacy, and environmental protection. The finding of the study is cultural heritage, and educations are positive and environmental protection, and health are negative significant relationship between ROA and cultural heritage, health, financial literacy, and education are significant relation with ROE. Similarly cultural heritage, education, health, and environmental protection are significant impact on ROA and cultural heritage, education, health, and financial literacy are significant impact on ROE.